Strength performance of concrete made using wastewater from the UP Lagoon - Dela Cruz, Gene Euclid T.; Gonzales, Karla Fatima
Conservation and preservation of freshwater is increasingly becoming important as the global population grows. This study reports experimental findings regarding the use of partially treated lagoon wastewater from the UP lagoon as alternatives to potable water in mixing concrete. Water samples was characterized and proportioned in varying amounts in each concrete mix. Setting times for each sample was taken and the concrete samples were tested for compressive strength within 7, 14 and 28 days. Leaching was quantified using TCLP and photometer analysis. Assessment of performance was accomplished by comparing the compressive strength, setting time and leaching of the samples to a control sample made using potable water. Results showed that the water qualities from UP lagoon are within the tolerable limits which suggest that using wastewater from UP lagoon will pose no significant harm on concrete quality. The compressive strength of concrete increases as the water to cement ratio is decreased. Longer curing period show development in strength from 7 to 28 days. Variation in wastewater concentration did not affect the compressive strength of concrete as compared to potable water. It is found out that as wastewater concentration is increased, setting time also increased. TCLP showed that chloride content leached within tolerable limits. In conclusion, UP lagoon wastewater can be used as an alternative to potable water without compromising the quality of concrete produced. It is recommended to increase the number of sample or trials to ensure reliability of results with regards to compressive strength and setting time and to measure more water properties to reinforce the results.